Ag3PO4-Red Banyan Fruit Extract (Ficus benjamina. L) Nanocomposite for Degradation of Detergent Waste - Muhammad Ihram Basri; Komang Sri Devi Wahyuni; Yolanda Liambo Tamallum; La Ode Ahmad Nur Ramadhan; Abdul Haris Watoni (Syarif Hidayatullah State Islamic University, 2019)
Detergents waste containing SDS (Sodium Dodecyl Sulfate) still becomes a major environmental problem that must be overcomed. The degradation of SDS by silver phosphate (Ag3PO4)-Red Banyan extract nanocomposite was performed under visible light. This research aimed to determine the percentage decrease in SDS concentration under visible light by using Ag3PO4 facilitated extract of red banyan fruit. The Ag3PO4-Red Banyan extract nanocomposite was prepared by coprecipitation method and facilitated by a red banyan extract solvent. The result showed that the silver composite phosphate (Ag3PO4) facilitated red banyan extract had a percentage of SDS degradation i.e. 85.9% for 2 hours. This result showed that the silver composite phosphate (Ag3PO4)-a red fruit extract becomes a promising ingredient for degrading SDS in aquatic environment environments.